2020
DOI: 10.1016/j.ijfatigue.2020.105593
|View full text |Cite
|
Sign up to set email alerts
|

Influence of moisture and drying on fatigue damage mechanisms in a woven hemp/epoxy composite: Acoustic emission and micro-CT analysis

Abstract: For the last 20 years, plant fibres have emerged as an alternative to glass fibres in composites.However, a crucial issue with plant fibre composites is their durability, i.e. their long-term hygrothermal and fatigue performances. This study deals with the influence of different conditionings (Ambient, Wet and Wet/dry) on the fatigue behaviour of [(±45)] 7 hemp/epoxy composites. The induced damage mechanisms are investigated by acoustic emission and micro-CT. Results show that the Wet samples exhibit the lowes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 58 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…Among these, it is possible to find the model proposed by D'Amore et al, based on the residual strength degradation of the composite [47]. This model was developed for glass-mat-reinforced thermoset based composites, but it was proved to be able to successfully predict the fatigue behaviour of continuous glass fibre reinforced composites [48,49] and woven hemp/epoxy composites [25]. The model proposed by D'Amore et al was used as a basis for the development of the Epaarachchi and Clausen model [50], used in the present study.…”
Section: Modelling Of Fatigue Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Among these, it is possible to find the model proposed by D'Amore et al, based on the residual strength degradation of the composite [47]. This model was developed for glass-mat-reinforced thermoset based composites, but it was proved to be able to successfully predict the fatigue behaviour of continuous glass fibre reinforced composites [48,49] and woven hemp/epoxy composites [25]. The model proposed by D'Amore et al was used as a basis for the development of the Epaarachchi and Clausen model [50], used in the present study.…”
Section: Modelling Of Fatigue Lifementioning
confidence: 99%
“…off-axis plies, moisture content, fibre crimp, 'out-of-plane' weaves in fabric) are all influencing longevity of plant fibre composites. Regarding the moisture content, Barbiere et al [25] have recently demonstrated the influence of the storage and the testing conditions on fatigue behaviour of a woven hemp/epoxy composite. Liang et al [26], in their study, showed that the [±45] 3S flax/epoxy specimens offer better specific fatigue endurance than similar glass/epoxy laminates, which was not the case for the [0/90] 3S specimens.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, contrary to most petrosourced composites, PFCs are highly sensitive to hygrothermal conditions and their variation and/or cycling over time [13]. Their monotonic, fatigue and vibrational behaviours are reported to be significantly influenced by such parameters [8,9,[14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid composites exhibit damage patterns that are mostly dominated by the higher fibre volume fraction of glass fibres and their location in the outermost layers (Boria et al, 2020). For applications that have to withstand dynamic loads, the determination of the fatigue behaviour of composites is also of particular interest (Yuanjian and Isaac, 2007;de Vasconcellos et al, 2014a;de Vasconcellos et al, 2014b;Fotouh et al, 2014;Shahzad and Isaac, 2014;Barbière et al, 2018;Barbière et al, 2020). Compared to GFC, HFC shows lower fatigue sensitivity and lower stiffness degradation at the same normalised peak stress levels and better resistance to crack formation (Yuanjian and Isaac, 2007;Shahzad and Isaac, 2014).…”
Section: Introductionmentioning
confidence: 99%